Groundwater in fractured granite for water supply to remote areas in Malaysia - Sapari, Nasiman (IWA Publishing 2010, 2010)
Groundwater in fractured granite in Malaysia was found to be an economical source of water supply for various remote industries and communities. The uses include for agricultural processing, mineral water bottling, granite quarry, golf course irrigation and drinking water supply. Forty five tubewells belong to private companies operating in various places in the area were evaluated in terms of the yields and water quality. The wells were drilled using rotary air-percussion method to a maximum depth of 200 m and provided with 6 inch PVC casing and screens.